2017
DOI: 10.5935/0103-507x.20170013
|View full text |Cite
|
Sign up to set email alerts
|

Chronic critical illness: are we saving patients or creating victims?

Abstract: The technological advancements that allow support for organ dysfunction have led to an increase in survival rates for the most critically ill patients. Some of these patients survive the initial acute critical condition but continue to suffer from organ dysfunction and remain in an inflammatory state for long periods of time. This group of critically ill patients has been described since the 1980s and has had different diagnostic criteria over the years. These patients are known to have lengthy hospital stays,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 72 publications
2
51
0
6
Order By: Relevance
“…Among the aspects addressed in the "Deficiency of physical structure and human resources" category, there is work overload, linked to the dimensioning of personnel below what is necessary and the precariousness of physical infrastructure and equipment. Therefore, even though hospitalization by court order is a problem in the Brazilian reality (3)(4)(5)(12)(13)(15)(16) , international and national studies address the issue of cost rationalization and access to ICU beds (4,12,24) . Rationing is the allocation of health care resources with limited availability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the aspects addressed in the "Deficiency of physical structure and human resources" category, there is work overload, linked to the dimensioning of personnel below what is necessary and the precariousness of physical infrastructure and equipment. Therefore, even though hospitalization by court order is a problem in the Brazilian reality (3)(4)(5)(12)(13)(15)(16) , international and national studies address the issue of cost rationalization and access to ICU beds (4,12,24) . Rationing is the allocation of health care resources with limited availability.…”
Section: Discussionmentioning
confidence: 99%
“…competing interests and that influence in the decisions in the screening and inadequate communication with patient families (1,(12)(13)(14)(15) .…”
Section: Introductionmentioning
confidence: 99%
“…Even when in some cases, the diagnosis needs to be confirmed after the resolution of the sepsis, the previous studies suggest that many of the diseases found during critical illness may persist 20 . Special efforts must be made to detect relevant comorbidities that may affect the short-term outcome of patients with CO-VID-19, but also to avoid turning them into longterm victims of their complications 21 . Obesity is a preventable, treatable, but relapsing disease 22,23 that will warrant further attention and interventions for the COVID-19 survivors and for the general population, since other pandemics may arise in the future 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, there has been growing interest in the study of chronically critically ill patients who survive the initial acute insult but cannot be weaned from life support, therefore requiring prolonged hospitalisation, which increases the demand for resources. Such patients develop immune exhaustion due to the combination of invasive procedures and morbidity, promoting prolonged hospitalisation and a higher incidence of HAI [17,18].…”
Section: Plos Onementioning
confidence: 99%